Pemeriksaan Kesehatan Umum pada Pengunjung Wisata Pulau Merah Berbasis Community Care - Desy Purnamasari; Erlin Novitasari; Lutvia Dwi Rofika; Desi Trianita (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
With the increasing number of people experiencing long-term and worsening illnesses such as hypertension, cholesterol, diabetes, and gout, it is recommended that the public regularly check their health, especially for blood pressure, blood sugar, cholesterol, and uric acid levels, to prevent complications that can last a long time and have major impacts. The purpose of this community service is to improve the health of tourists and the surrounding community through promotional, preventive, and early detection efforts for health problems by involving the active participation of the local community. Providing free health check-ups to the community, especially those living on Pulau Merah Beach, using tensiometers, weight scales, and GCU meters. This activity was carried out in January at the Pulau Merah Beach Tourism Area. The results of the health check-ups showed that most visitors had normal blood pressure (61.90%), and normal blood sugar levels (74.60%), most had normal uric acid levels (55.56%). The free health check-ups showed that most visitors had normal results. This activity plays an important role in promotional, preventive, and early detection efforts for chronic diseases such as high blood pressure, cholesterol, diabetes mellitus, and gout. By involving active community participation, this activity is expected to increase awareness and the health level of tourists and the surrounding community in order to prevent complications of chronic diseases in the future.